Discordant Voting Protocols for Cyclically Linked Agents - Pongrácz, András (The Electronic Journal of Combinatorics, 2020)
Voting protocols, such as the push and the pull protocol, model the behavior of people during an election. These processes have been studied in distributed computing in peer-to-peer networks, and to describe how viruses or rumors spread in a community. We determine the asymptotic behavior of the runtime of discordant linear protocols on the cycle graph and the probability for each consensus to win.